Relasi antara Pergeseran Peran Pencari Nafkah dan Krisis Maskulinitas dalam Cerpen “Huruf Terakhir” karya Benny Arnas - Marta Widyawati (Jurnal Bahasa dan Sastra, 2021)
This research aims to show the masculinity crisis experienced by a male character (a husband) due to the shift role of breadwinner in marriage in the short story "Huruf Terakhir" by Benny Arnas. This research is essential because it can demonstrate the impact of the wife's involvement to work in the public domain towards the husband's condition. This research is qualitative research by utilizing the concept of gender. Data collection techniques are carried out through document tracing on a short story "Huruf Terakhir" by Benny Arnas as the corpus.  The data obtained was analyzed using descriptive analysis method. The results showed that shifting role of breadwinner can cause a man (a husband) to experience a crisis of masculinity such as loss of independence, confidence, courage, assertiveness, and emotional control. The shifting role as breadwinner is also shown to open the opportunities for repression in women. Therefore, the research on the short story "Huruf Terakhir" is expected to contribute to the study of gender-sensitive literature, especially since it is able to show masculinity traits associated with the role of breadwinner can complicate men’s position and  potentially hinder women's freedom.